Electron beam irradiated nanocomposite for gas barrier application - Anuar, Hazleen; Jamal, Nur Ayuni; Abd Razak, Shamsul Bahri (2011)

(untitled)
Polyolefins, such as polypropylene and polyethylene find extensive use in packaging. Improvements in poor barrier properties of polyolefins will be beneficial for the current applications and should also lead to applications in pharmaceuticals, electronic packaging and particularly packaging of food products, which are sensitive to oxygen. Most schemes to improve polyolefins gas barrier property involve either addition of higher barrier plastics via a multilayer structure or high barrier surface coatings, however, these approaches are not cost effective. The emerging field of polymer-layered nanocomposites is unique in that it addresses shortcomings of polyolefins for both packaging and engineered applications requiring desirable mechanical, thermal as well as good barrier properties.